2019
DOI: 10.1111/1365-2745.13143
|View full text |Cite
|
Sign up to set email alerts
|

Plant geographic origin and phylogeny as potential drivers of community structure in root‐inhabiting fungi

Abstract: Root‐inhabiting fungal communities, including mutualists and antagonists, influence host plant performance, and can potentially shape plant community composition. However, there is uncertainty about how root‐inhabiting fungal communities are structured, and if fungal community characteristics are significant predictors of host plant abundance. In this study, we first assessed how root‐inhabiting fungal communities were structured in relation to the phylogeny and geographic origins (native vs. exotic) of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 129 publications
6
19
0
Order By: Relevance
“…In our research we focused on another Solidago species, outside its native range. In accordance with (Koyama et al 2019) Cladosporiaceae was identified as an abundant fungal family in the two habitat types under investigation. However, an opposite, positive correlation between Cladosporiaceae and Solidago gigantea was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In our research we focused on another Solidago species, outside its native range. In accordance with (Koyama et al 2019) Cladosporiaceae was identified as an abundant fungal family in the two habitat types under investigation. However, an opposite, positive correlation between Cladosporiaceae and Solidago gigantea was observed in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Recently (Koyama et al 2019) studied root-inhabiting fungi in a wide range of native and exotic plant species in Canada. The plant selection included Solidago canadensis , in this context a native plant species.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for mycorrhizal fungi, which form mutualisms with plants, and for which host specificity is an important geographical constraint on species distributions (Sato, Tsujino, Kurita, Yokoyama, & Agata, 2012). Hence, studies of community structure and biogeographical patterns of soil fungi are significantly improved when data on plant diversity and distributions are included within their models (Koyama, Maherali, & Antunes, 2019; Pellissier et al., 2014; Vályi, Mardhiah, Rillig, & Hempel, 2016). To this end, the FungalRoot database (Soudzilovskaia et al, 2020) provides key data on mycorrhizal associations with which to study the macroecology and biogeography of these interactions.…”
Section: Biotic Considerationsmentioning
confidence: 99%
“…Some of these traits are difficult to measure, which may explain why data are sparse. Traits relating to some of these interactions may be phylogenetically conserved (e.g., shared pathogens or mutualists; Chen et al., ; Koyama, Maherali, & Antunes, ), highlighting the complementary role of phylogenetic relationships in studies of invasion.…”
Section: Trait Selectionmentioning
confidence: 99%